The contradictory views on ancient literary works as a foundation of world historical development - Yaacob, Solehah@Nik Najah Fadilah; Haron, Ismail (2020)
Contradictory views on ancient literary works provide a panorama of historical development. However, the validity of the texts was considered as issue of prime importance. The critics on its literary authenticity would reveal whether it was real or just a fabrication. The Epic Gilgamesh was ascertained by Said Ghanimi to be unauthentic. The contentions by S. N. Kramer and Taha Baqir were with regard to the differences of language usage in the Epic Gilgamesh either Sumerian or Akkadian as well. The acknowledgment of the West on Iliad and Odyssey by Homer as the first document written in world history was unfounded although this was highlighted by B. Lansberger in 7th conference in Paris on 1958. The Code Hamurabbi is a well preserved Babylonian Code of laws, unfortunately, it was considered as a fabrication of Old Testament which came 800 years later, especially on the narration of Big Flood Story as mentioned in the Book of Genesis. It is regrettable that the paucity of materials on the ancient history of the ancient people available from the Muslim sources poses as constrain on this study. The research is compelled to refer almost entirely to Western and Jews sources. Thus, the approach used in this study is based primarily on historical and linguistic analysis of ancient literary works.